2022
DOI: 10.17582/journal.pjz/20200510140530
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Temperature Variations on Breeding Behavior of Cirrhinus mrigala during Induced Spawning

Abstract: Authors' Contributions MT conceived the idea, provided guidance for the studies and manuscript write-up. AA performed experimental work. ASH, AN, SF and SS facilitated the conduction of experiments. ARA and MW helped in data analysis and manuscript write-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Temperature has great impact on fish fertilization rate. Increase in temperature up to optimum boosting the fertilization rate (Iqbal et al, 2021). The present study also reveals the comparison of Rohu (Labeo rohita) and Mrigala (Cirrhinus mrigala) fertilization rate.…”
Section: Impact Of Temperature Variation On Fertilization Ratesupporting
confidence: 56%
See 3 more Smart Citations
“…Temperature has great impact on fish fertilization rate. Increase in temperature up to optimum boosting the fertilization rate (Iqbal et al, 2021). The present study also reveals the comparison of Rohu (Labeo rohita) and Mrigala (Cirrhinus mrigala) fertilization rate.…”
Section: Impact Of Temperature Variation On Fertilization Ratesupporting
confidence: 56%
“…Ovulation rate, spawning response, fertilization and hatching rate were directly influenced by temperature (Iqbal et al, 2021). It was observed that increased in temperature decreased the latency period in fishes (Phelps et al, 2007).…”
Section: Effects Of Temperature Variation On Spawning Response Timementioning
confidence: 99%
See 2 more Smart Citations